2016
DOI: 10.29245/2572.942x/2016/8.1084
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study for remote assessment of cognitive function in multiple sclerosis

Abstract: Background-Cognitive impairment is common in multiple sclerosis (MS), and affects employment and quality of life. Large studies are needed to identify risk factors for cognitive decline. Currently, a MS-validated remote assessment for cognitive function does not exist. Studies to determine feasibility of large remote cognitive function investigations in MS have not been published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…We showed that remote cognitive assessment of patients with hematological cancers is feasible and provides several advantages including efficiency, convenience, and automated scoring. This is consistent with previous studies supporting the feasibility of remotely measuring cognitive performance in other populations 19,28 . Additionally, although for this pilot study we restricted enrollment to English‐speaking participants, BrainCheck can be administered in multiple languages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We showed that remote cognitive assessment of patients with hematological cancers is feasible and provides several advantages including efficiency, convenience, and automated scoring. This is consistent with previous studies supporting the feasibility of remotely measuring cognitive performance in other populations 19,28 . Additionally, although for this pilot study we restricted enrollment to English‐speaking participants, BrainCheck can be administered in multiple languages.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with previous studies supporting the feasibility of remotely measuring cognitive performance in other populations. 19 , 28 Additionally, although for this pilot study we restricted enrollment to English‐speaking participants, BrainCheck can be administered in multiple languages. However, there are also several caveats to remote assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Depression was assessed as previously described. 29 Age at MS onset was confirmed by review of EHR. For each participant, we calculated the Multiple Sclerosis Severity Scale (MSSS), an indicator of disease severity using the Expanded Disability Status Scale and disease duration.…”
Section: Clinical Datamentioning
confidence: 89%
“…The aspects evaluated include therapeutic follow-up, remote assessment of functional status, use of technologies to aid in rehabilitation (telerehabilitation), remote neurocognitive assessment, remote psychological interventions, including cognitive-behavioral therapy, mindfulness, and neuropsychological rehabilitation, remote monitoring of activities, and assessment of adherence to medical therapy 19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 .…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Telemedicine was tested for neuropsychological and mental health assessment in MS patients 32 . Another study assessed the use of digital tools for neuropsychological rehabilitation in patients with MS 35 . These studies showed positive contributions of the use of technology both for the evaluation and for rehabilitation of these patients 32,35 .…”
Section: Multiple Sclerosismentioning
confidence: 99%